(untitled) (Academic Journal of Internal Affairs, 2020)
Nowadays British Armed Forces defend the United Kingdom and overseas territories, provide strategic intelligence and nuclear deterrence, support civil emergency organisations in times of crisis, defend the interests of the country by projecting power strategically and through expeditionary interventions, provide a defence contribution to UK influence and security for stabilisation. In March 2020 the Ministry of Defense also set up the COVID Support Force, which is responsible for strengthening civilian public services in particular with regard to public health (eg construction of military hospitals) and logistics (epidemiological assistance). The British Armed Forces are heavily involved in all of these tasks, except and provides the primary land force component necessary to achieve these tasks. During these heavy duties British soldiers have acquired the knowledge, skills and typical organizational culture that fundamentally differs from civilians’ skills. To prevent social conflicts and acquire civilian skills as well every state needs a broad set of tools of institutionalized human reconversion. Particularly important is the issue during application of volunteering forces when disarmament befalls at relatively young age and veterans are usually not expected to be reemployed by their previous employer. In general, this is a challenge at international level and the following solutions are offered in the UK.